2002
DOI: 10.1002/prot.10177
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the pKa of histidine side‐chains correlates with burial within proteins

Abstract: Acidic pKas of histidines buried within the protein interior are frequently rationalized on the contradictory basis of either polar interactions within the protein or the effects of a hydrophobic environment. To examine these relationships, we surveyed the buried surface area, depth of burial, polar interactions, and crystallographic temperature factors of histidines of known pKa. It has been found that buried environments of histidines do not always result in acidic pKas. Instead, the variability of histidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(171 citation statements)
references
References 34 publications
6
156
1
Order By: Relevance
“…A survey of pK a values of 39 different histidine residues from 13 different proteins (Edgcomb and Murphy 2002) showed that the pK a of imidazole groups (as measured by NMR spectroscopy) differed greatly from the regularly cited (''standard'') value of 6.3 (Thurlkill et al 2006) and ranged from 4.6 (His40 of bovine chymotrypsinogen) to 9.2 (His72 in tyrosine phosphatase). The physicalchemical basis for this variation is not completely understood (Edgcomb and Murphy 2002), but may be due in part to local variations in electrostatic potential. The value of pK a of aspartate-b-CO 2 H and glutamate-g-CO 2 H also vary widely in proteins (García-Moreno et al 1997).…”
Section: Chemical Modification Of A-amylasementioning
confidence: 93%
“…A survey of pK a values of 39 different histidine residues from 13 different proteins (Edgcomb and Murphy 2002) showed that the pK a of imidazole groups (as measured by NMR spectroscopy) differed greatly from the regularly cited (''standard'') value of 6.3 (Thurlkill et al 2006) and ranged from 4.6 (His40 of bovine chymotrypsinogen) to 9.2 (His72 in tyrosine phosphatase). The physicalchemical basis for this variation is not completely understood (Edgcomb and Murphy 2002), but may be due in part to local variations in electrostatic potential. The value of pK a of aspartate-b-CO 2 H and glutamate-g-CO 2 H also vary widely in proteins (García-Moreno et al 1997).…”
Section: Chemical Modification Of A-amylasementioning
confidence: 93%
“…41 Due to the high reactivity of tyrosinate/tyrosine residues towards diazonium reagents, the coupling has been reported to occur at pH as low as 4. 37 In the same study the authors reported that over the 4.0-9.0 interval of pH investigated, Tyr analogues had higher reactivity than the corresponding His derivatives.…”
Section: Scheme 1 Synthesis Of Poly(ethylene Glycol)-functional Anilmentioning
confidence: 99%
“…The histidine side chain pKa in proteins is known to vary considerably according to its environment. [19] Titratable histidines in proteins have been identified with a side-chain pKa as high as 9.2 and as low as 4.6. [19] Importantly, Coulombic interactions between neighboring side-chains in space, as predicted for amphipathic peptides [20] , would also be expected to depress the pKa.…”
Section: Biophysical Characterisationmentioning
confidence: 99%
“…[19] Titratable histidines in proteins have been identified with a side-chain pKa as high as 9.2 and as low as 4.6. [19] Importantly, Coulombic interactions between neighboring side-chains in space, as predicted for amphipathic peptides [20] , would also be expected to depress the pKa. Hence an acidic value for the side-chain pKa of histidine in LAH is neither unexpected nor is it likely to be as a result of either intra-or intermolecular hydrogen bonding.…”
Section: Biophysical Characterisationmentioning
confidence: 99%